2015
DOI: 10.1183/09031936.00119914
|View full text |Cite
|
Sign up to set email alerts
|

French multicentric validation ofALKrearrangement diagnostic in 547 lung adenocarcinomas

Abstract: Anaplastic lymphoma kinase (ALK) gene rearrangements in lung adenocarcinoma result in kinase activity targetable by crizotinib. Although fluorescence in situ hybridisation (FISH) is the reference diagnostic technique, immunohistochemistry (IHC) could be useful for pre-screening.Diagnostic yields of ALK IHC, FISH and quantitative reverse transcriptase PCR performed in 14 French pathology/molecular genetics platforms were compared. 547 lung adenocarcinoma specimens were analysed using 5A4 and D5F3 antibodies, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 28 publications
2
48
0
Order By: Relevance
“…22 Three of our 4 FISH+/IHC− cases also fell in this range (15–18%), in keeping with the results in that study. A recent study showed that approximately 6% of ALK FISH cases belong to a borderline group for which ALK FISH evaluation has of limited reliability possibly due to sampling effects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…22 Three of our 4 FISH+/IHC− cases also fell in this range (15–18%), in keeping with the results in that study. A recent study showed that approximately 6% of ALK FISH cases belong to a borderline group for which ALK FISH evaluation has of limited reliability possibly due to sampling effects.…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned earlier, the positive ALK FISH results in these 3 cases were borderline (15–18%), which might explain the discordances as observed in the recent French study. 22,23 ALK FISH in the remaining 1 FISH+/IHC− case showed break apart probes in 27% of tumor cell nuclei; this case showed BIRC6->EML4 and AAK->ALK fusions by both NGS of DNA and RNAseq. In our previous study 21 , we found EML4–ALK fusion by RT-PCR followed by sequencing in this case using FFPE.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, technical errors cannot be excluded reliably as the main reason for the discordant cases, particularly in FISH‐positive cases with negative IHC results. A similar finding was observed by Lantuejoul et al ., who reported that discordant ALK status between FISH and IHC occurred predominantly in cases with a percentage of positive tumour cells ranging between 10% and 20%.…”
Section: Discussionmentioning
confidence: 99%
“…We tested CA 19-9 expression, immunohistochemically (IHC), using the 116-NS-19-9 antibody (Covance Inc., Princeton, USA). We applied the expression score, which was described previously [2628]. Percentages of CA 19-9 + tumor cells (proportion score) was scored as 0: none (0 %); 1: 1–10 %; 2: 11–30 %; 3: 31–50 %; 4: 51–70 %; and 5: 71–100 % of each tumor sample.…”
Section: Methodsmentioning
confidence: 99%